Cashless Policy and Performance of Banks in Nigeria - Nene Wilson-Amadi; Emeka J. Okereke (Research Parks Publishers, 2023)
This study looks into the connection between Nigerian banks' performance and their cashless policy. Checks, credit/debit cards, and NEFT were used as stand-ins, and profitability was used as a performance indicator, in order to analyse the synergy between Nigerian banks' performance and their cashless strategy. The study adopted quasi-experimental research design using cross-sectional research design. The population of this study comprised of 10 selected banks in South-South State, Nigeria. 100 copies of questionnaire distributed to top managers of these selected banks. The Multiple Regression Analysis Statistical tool was used with the aid of Statistical Package for Social Sciences (SPSS version 23.0), discriminant validity (AVE) and Cronbach Alpha verified the internal consistency and validity status and the results were positive. The findings of the study showed that cashless policy substantially related with performance of banks in Nigeria, thus enhancing profitability. Based on the findings, the study, recommends that, Making use of cheques, funds transfers, E –payments and owning/ operating of bank accounts should be encouraged. This will give a further boost to the enrichment of our payment system in Nigeria.